Attitudes Towards the Implementation of School Digital Citizenship - Latifah Purwanti; Selnistia Hidayani; Fadilla Oktaviana (Tarbiyah Departement collaboration with AMCA, 2023)
In the current era, marked by the impact of globalization and the increasing prevalence of digital technologies, students are faced with the imperative to acquire a diverse range of skills for the future, with a specific focus on digital citizenship. These forward-looking competencies hold significant importance in addressing a multitude of educational challenges, particularly those associated with school policies and forthcoming practices. Consequently, the primary objective of this research is to evaluate students' perspectives regarding the integration of digital citizenship principles at the secondary school level, specifically within one of the Islamic Secondary Schools situated in Serang Banten. This qualitative descriptive study encompassed the participation of 120 students from Islamic Middle Schools and was executed through the administration of a questionnaire designed to explore the technology students employ within their school environment. The outcomes of the research revealed an average score of 30 across all questionnaire items, indicating an increasing adoption of digital media alongside a level of technology misuse exceeding the norm. As a result, it is strongly advised that both school administrators and digital teams gain a profound understanding of students' digital requirements concerning the future direction of their educational institutions. Given these findings, the researchers advocate for further investigations into the implementation of digital citizenship within school districts, taking into account diverse facets, including school administrators and educators.